FACTORS INFLUENCING THE AVAILABILITY OF GREEN OPEN SPACE IN EAST SURABAYA - Erma Fitria Rini; Haryo Sulistyarso; Adjie Pamungkas (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2014)
Air pollution in Surabaya is the greatest and urgent issue to be solved. East Surabaya has the largest CO2 emissions from housing activity compared to other Surabaya regions. One of the ways to naturally absorb CO2 is to provide adequate green open space. Public green open spaces in East Surabaya amounted to only 2.37% of the total land area. The objectives of this study is to know the availability of Green open spaces and factors influencing it’s availability in East Surabaya, compare to area of formal housing and kampung. Descriptive analysis is used to explain the availability of Green open space. Content analysis is used in this research to find the factors influence availability of green open spaces. The result shows that East Surabaya has 644.42 ha green open space or only 7.14%. The result also shows that factors influence the availability of green open spaces in East Surabaya are different between formal housing and kampung. Some factors related to the policy and social aspects that influence the availability of green open space in both East Surabaya kampung and formal housing. Those factors are: the allocation of green open space in spatial planning; forestation program; basic green coefficient; incentives and disincentives; supervision and control of landuse; community participation; the influence of community leaders; public awareness; communities; reward in forestation programs; facilitators; and the diversity of greening innovation. Meanwhile, some factors such as the limited land, the housing density, the changes in land use, and the limited fund has only influence in kampung. Factors of coordination between government agencies and developers and also the concept offered by developers have only influence in formal housing.